Search of resistance sources to potato wart Synchytrium endobioticum (Schilbersky) Percival causative agent - Zelya, A.; Zelya, G.; Olyinik, T.; Pisarenko, N.; Zakharchuk, N. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2024)
Goal. To evaluate and to choose potato varieties breeding material resistant to wart and search resistance sources to causative agent of potato wart Synchytrium endobioticum (Schilbersky) Percival.Methods. The study involved 739 samples breeding of potatoes varieties Institute for potato study NAAS and its’ Polissian division in 2020—2022. The samples were received by different parents forms crossings. Evaluation of breeding material for resistance to common 1(D1) and aggressive pathotypes of potato wart was performed in the laboratory conditions of the Ukrainian Science Research Plant Quarantine Station IPP NAAS on an artificial infectious background according to EPPO Standard PM 7/28/1 and EPPO Standard PM 7/28/2 and «Techniques or evaluation and choice of potato breeding material resistant to wart Synchytrium endobioticum (Schilb.) Perc harmonized as per EU requirements» and in field conditions of pathogen spread.Results. A 699 potato samples (94.6%) from 739 hybrids from 2022-through 2022 received resistant value to common pathotype of wart causative agent. 40 (5.4%) samples were defeated by disease causative agent and they were rejected by us. The researches results showed that 21 outlet potato parents forms had the highest resistance degree (1.2—2.0 points). They recommended for the following usage in in breeding process as a resistance source to potato wart. Hybridological analysis for potato resistance inheritance provided on the following variants of parents forms crossing F09.209-3/P14.3/12, Svitana / Mezhzyrichka, Vyhoda / Svitana, Radmysl / Svitana,Vzirets / Svitana, P10.10/35/Svitana. 81.13.9/1/Svitana, P12.14-8/Partner, Zvizdal/P10.109/35, Mezhyrichka/Sncedar, Levada /Rostovytsya, Svitana Rostovytsya, Nagoroda Rostovytsya / Rostovytsya, ВМ12.24-15 /Vygoda, Floatka/Rostovytsya, Mezhyrichka/Dorogyn, Agave/Aria, 08.102/4/Miranda, Ivankivska rannya/Alliance, Vectar/Radmysl; Charunka/Alliance; Tyras/89.715с88. The potato resistant inheritance showed 100% to wart. The crossing variant F 09.209-3 / P10.9-3, P09.26-2/Alliance gave 50.0% resistant inheritance. The crossing variant Myroslava/Н.07.162-1 gave 88.9% resistant inheritance.Conclusions. There were chosen 699 (94,6%) among 739 potato samples in 2020—2022 resistant to common pathotype. Hybridological analysis for potato resistance inheritance to wart showed that variant resistant (♀) × resistant (♂) give 100% resistance to wart potato inheritants. The most resultative resistant potato samples choice was resistant to D1 (common) and 22 (Bystrysia) agressive pathotype during potato breeding studies with complex resistance to wart pathotypes in 2021—2022. The most virulent was 18 (Yasynnia) aggressive pathotype. There were only 5 (21.7%) resistant to this wart pathotype. Chosen samples with complex resistance to wart pathotypes recommended for the following usage in breeding. They recommended for improve in disease sources and for the following usage in breeding process as potato resistance sources to disease causative agent and for the improving in disease sources.